PENDIDIKAN ISLAM DI PESANTREN ANTARA TRADISI DAN TUNTUTAN PERUBAHAN - Noor Hafidhoh (MUADDIB Jurnal Kependidikan dan Keislaman, 2016)
Pesantren as the oldest Islamic educational institutions in indonesia, are required to be balanced in seeking the modernization of schools and maintain the originality of its culture and traditions. Religious boarding is a characteristic that didnt have Islamic educational institutions other, its Islamic schools or madrasah. However, schools do not have to shut down, it opens in following the demans of the times. To face these changes, the exponents boarding looks unhurried, institutional transform schools into a modern educational institution Islam all the way, but instead tend to retain the wisdom of traditional daily. They accept the modernization of Islamic education only in a very limited scale, extent be able to ensure the schools can survive